Enter the Matrix: Fibroblast-immune cell interactions shape extracellular matrix deposition in health and disease. [version 2; peer review: 1 approved, 2 approved with reservations] - Anthony Altieri; Grace V. Visser; Matthew B. Buechler (F1000Research)
Fibroblasts, non-hematopoietic cells of mesenchymal origin, are tissue architects which regulate the topography of tissues, dictate tissue resident cell types, and drive fibrotic disease. Fibroblasts regulate the composition of the extracellular matrix (ECM), a 3-dimensional network of macromolecules that comprise the acellular milieu of tissues. Fibroblasts can directly and indirectly regulate immune responses by secreting ECM and ECM-bound molecules to shape tissue structure and influence organ function. In this review, we will highlight recent studies which elucidate the mechanisms by which fibroblast-derived ECM factors (e.g., collagens, fibrillar proteins) regulate ECM architecture and subsequent immune responses, with a focus on macrophages. As examples of fibroblast-derived ECM proteins, we examine Collagen Triple Helix Repeat Containing 1 (CTHRC1) and Transforming Growth Factor-β-inducible protein (TGFBI), also known as BIGH3. We address the need for investigation into how diverse fibroblast populations coordinate immune responses by modulating ECM, including the fibroblast-ECM-immune axis and the precise molecular mediators and pathways which regulate these processes. Finally, we will outline how novel research identifying key regulators of ECM deposition is critical for therapeutic development for fibrotic diseases and cancer.